Two-stage Energy Management of Residential Microgrid Community using Pairing Strategy - Ju, Chengquan (2017)
A generalized two-stage energy management model in the context of interconnected microgrid (MG) community is proposed in this paper. Total operational cost minimization of the community and benefits of MG partners are both investigated. In the lower stage, based on the detailed model of individual MG with multiple energy sources and loads, the distributed MG-level EMS solves the optimization problem to decide the optimal energy dispatch based on the interest of MG owners. In the upper stage, a pairing strategy is proposed in the community-level EMS to explicitly determine the power flow between MGs and with the upstream distribution grid. The profit by minimized energy exchange with the distribution grid is fairly shared by participants in the MG community. With the proposed structure and control algorithm, the user preference of each MG is reserved and user privacies are well preserved. Simulation studies successfully demonstrate the effectiveness that the proposed two-stage energy management model can effectively allocate the power flow among different MGs while the minimal operational cost of the community is achieved.